Nurturing Rural Women Leaders for Upscaling Climate-resilient Farming Strategies: Analyzing the Post-intervention Social Networks in the North and South 24 Parganas Districts of West Bengal, India - Misra, Sanchayeeta; Chadha, Deepali; Mukhopadhyay, Prama; Das, Suvangini; Kar, Diksha; Puskur, Ranjitha; Gartaula, Hom Nath (International Rice Research Institute, 2025)
This report focuses on the impact of targeted capacity-building initiatives implemented as part of Work Package 2 - EMPOWER (Bundled Innovations for Women’s Empowerment and Resilience) within the CGIAR Initiative on Gender Equality (HER+). The research was conducted in two villages in West Bengal state of India: Balarampur in South 24 Parganas district and Makaltala in North 24 Parganas district. Women farmers in these areas face numerous challenges rooted in complex social dynamics, including traditional gender roles and institutional barriers that limit their access to resources and decision-making processes. This report builds on the foundational findings of the pre-intervention study, which demonstrated how Social Network Analysis (SNA) can be used to explore how women livestock farmers in West Bengal share essential knowledge to address the challenges posed by climate change and enhance their farming practices. This analytical approach revealed significant information gaps in poultry and goat farming, which hindered these farmers’ ability to adapt to environmental changes, improve productivity, and ensure food security for their families and communities. Additionally, the report highlighted the crucial role of community leaders who facilitate knowledge sharing, acting as intermediaries who connect farmers to valuable resources and information. These community leaders have actively engaged in capacity-building and training programs developed through the STIBs (Socio-technical Innovation Bundles) approach. By enhancing their skills and knowledge through these initiatives, they play a vital role in promoting sustainable agricultural practices, thereby contributing to the overall resilience of their communities. Their involvement helps create a supportive environment in which women livestock farmers can thrive despite the challenges they face, such as limited access to resources, information, and training. This study evaluates the effectiveness of the interventions designed to address the issues and knowledge gaps identified in the pre-intervention phase, specifically focusing on how the initiatives have influenced the empowerment and resilience of women engaged in livestock rearing. By outlining the objectives in both phases, this report aims to provide a comprehensive understanding of the impact of the interventions and to compare the findings with the pre-intervention results, ultimately highlighting the transformative potential of empowering women in agriculture.